The Cat that ThereforeIAm - Marjanić, Suzana (Poznańskie Studia Slawistyczne, 2022)
This is a review of the cat-related exhibition Little Measure of All Things and spoken word, a musical performance Life is Ca’ah, a collaboration with musician Dalibor Zovko, at the opening of the exhibition by artist, researcher and activist Ivana Filip, Atelier Žitnjak, curator: Bojan Krištofić, Zagreb, March 25–April 16, 2022.